2017
DOI: 10.1177/1069397117707184
|View full text |Cite
|
Sign up to set email alerts
|

A “Cognition and Practice” Approach to an Aspect of European Kinship

Abstract: Despite the long history of kinship studies, we still lack agreed theories capable of explaining the connection between terminological systems and kinship practice. This article argues for a cognitive approach centering on two distinct but complementary aspects of identity. It is argued that patterns of shared identity are implied by terminology and combine with other factors to motivate practice-in a feedback loop which transmits influences between terminological systems and political and economic institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The sociolinguistic emphasis on context-based semantic term manipulation could replace "culture" comparisons with context-based, or "event-based" (Chrisomalis, 2006), cross-cultural research to better inform ethnological interpretation on prehistory. Some efforts are already underway to develop ethnological databases to explore kinship and agency (e.g., Carmichael & Rijpma, 2017), specifically the relation between kin terminology and practice (e.g., Heady, 2017). Inevitably, however, any assumptions and interpretations using nonprehistoric data need to be tested archeologically with data from prehistory.…”
Section: Resultsmentioning
confidence: 99%
“…The sociolinguistic emphasis on context-based semantic term manipulation could replace "culture" comparisons with context-based, or "event-based" (Chrisomalis, 2006), cross-cultural research to better inform ethnological interpretation on prehistory. Some efforts are already underway to develop ethnological databases to explore kinship and agency (e.g., Carmichael & Rijpma, 2017), specifically the relation between kin terminology and practice (e.g., Heady, 2017). Inevitably, however, any assumptions and interpretations using nonprehistoric data need to be tested archeologically with data from prehistory.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that social relationships are linked to better health in several ways; however, this is only in theory and may vary in practice (13). Heady and Grandits (13) further mention that social relationships play several vital roles, including providing emotional benefits such as intimacy, a sense of belonging, and self-esteem. Through physical assistance, such as money, goods, services, and advice, social relationships continue to offer instrumental help (14).…”
Section: An Analysis Of the Role And Perceptions Of Social Relationsh...mentioning
confidence: 99%
“…This principle is the plankton supporting squid, crustaceans, fish, and whales. This basic understanding is most easily expressed when we take a filiocentric perspective on group-based kin terminology (after Moore 1988) and consider Heady's (2017) emphasis on the dialectic interaction between terminology and social practice to express identity, which itself is similar to Turner's (2012) objective-subjective cognitive "schema." The following filiocentric perspective-indicating how individuals apply terms not to genealogical relations but to entire groups in which they have a genealogical connection-is actually common to contemporary textbook explanations of kin terminology and is exemplified in Crow-Omaha by Trautmann's (2012:43-45) more elaborate presentation of group-based terms by gender.…”
Section: Kin Terminologymentioning
confidence: 99%
“…Likewise, once examined with historical evidence, the dogma of homogeneous German and East versus West European "ethnic patterns" of residence practices falls apart. Practices historically varied by socioeconomic contexts within and across the imagined boundaries (Heady 2017;Szołtysek 2008Szołtysek , 2012Szołtysek , 2015Szołtysek and Ogórek 2020;Szołtysek et al 2014). These findings are not restricted to European societies but also to indigenous peoples worldwide (as above).…”
Section: The New Old Synthesismentioning
confidence: 99%
See 1 more Smart Citation